Financial development and economic growth in Malaysia / Nur Amalina Maskor - Maskor, Nur Amalina (2017)
This paper aims to investigate the financial development and economic growth in Malaysia. The financial developments may cause the economic growth and vice versa in Malaysia that can affect the country. The dependant variable in this study is economic growth that will be measure by Growth Domestic Product (GDP). Three selected independent variables in this study are the foreign direct investment, trade, and stock trade. The data from the sample are pooled for 30 years (1986 - 2015). The data can be obtained from the World Data Bank. Interactive software package E-view 8.0 that would be used for testing and analyzing the data collected and a multiple linear regression is used in this study. This study used quantitative secondary data which is time series and multiple regression models represented by the ordinary least squares (OLS) as the technique to look the financial development and economic growth in Malaysia. The result show foreign direct investment has negative relationship with the economic growth same with the trade has negative relationship, while the stock trade has positive relationship with the economic growth.